It seems like you want to solve an equation involving \(7x - 4\). However, your equation is not very clear. It appears that you may be stating:
\[ 3 = \frac{2}{3}(7x - 4) \]
If this is the case, let's solve it step by step.
- Start with the equation:
\[ 3 = \frac{2}{3}(7x - 4) \]
- To eliminate the fraction, multiply both sides by 3:
\[ 3 \cdot 3 = 2(7x - 4) \]
This simplifies to:
\[ 9 = 2(7x - 4) \]
- Next, distribute the 2 on the right side:
\[ 9 = 14x - 8 \]
- Add 8 to both sides:
\[ 9 + 8 = 14x \]
which simplifies to:
\[ 17 = 14x \]
- Finally, divide both sides by 14 to solve for \(x\):
\[ x = \frac{17}{14} \]
Therefore, the solution is:
\[ x = \frac{17}{14} \]
If this was not what you intended, please provide additional context or clarify the equation.